Pengaruh Edukasi Video Terhadap Tingkat Pengetahuan Bahaya Tidak Sarapan Pagi Pada Siswa Sekolah Dasar SDN Gatot Subroto Kota Bandung - Mira Meliyanti (stikes dharma husada bandung, 2021)
Breakfast for children”s growth and development. But often if ignored, this can pose a risk to health and learning achievement. of knowledge of elementary school students about the dangers of not having breakfast before education with video, knowing the level of knowledge of elementary school students about the dangers of not having breakfast after education with video. The research design was a quasi-experimental study with pre-test and post-test designs. The number of research subjects was SDN students. The data collected were questionnaire pre test and post test. The results showed that on average before video education had good rsults, namely 252 (78.0%) and after video eduvation had and significant increase of 307 (95.0%).